2020
DOI: 10.1101/2020.05.11.083030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nance-Horan Syndrome-like 1 protein negatively regulates Scar/WAVE-Arp2/3 activity and inhibits lamellipodia stability and cell migration

Abstract: Cell migration is important for development and its aberrant regulation contributes to many diseases. The Scar/WAVE complex is essential for Arp2/3 mediated lamellipodia formation during mesenchymal cell migration and several coinciding signals activate it. However, so far, no direct negative regulators are known. We have identified Nance-Horan Syndrome-like 1 protein (NHSL1) as a novel, direct binding partner of the Scar/WAVE complex, which co-localise at protruding lamellipodia. This interaction is mediated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 46 publications
5
20
0
Order By: Relevance
“…Yet the extracts prepared from NHSL1-depleted cells and those prepared from cells simultaneously depleted of PPP2R1A and NHSL1 were as competent as wild type extracts in supporting actin polymerization. Both PPP2R1A and NHSL1 were detected associated with GTP-bound RAC1 Q61L (Fig.S4), in line with the fact that both CYFIP1 and NHSL1 harbor binding sites for active RAC1 7,16 . Together, these results show that PPP2R1A requires NHSL1 to regulate cell migration and actin polymerization.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Yet the extracts prepared from NHSL1-depleted cells and those prepared from cells simultaneously depleted of PPP2R1A and NHSL1 were as competent as wild type extracts in supporting actin polymerization. Both PPP2R1A and NHSL1 were detected associated with GTP-bound RAC1 Q61L (Fig.S4), in line with the fact that both CYFIP1 and NHSL1 harbor binding sites for active RAC1 7,16 . Together, these results show that PPP2R1A requires NHSL1 to regulate cell migration and actin polymerization.…”
Section: Resultssupporting
confidence: 66%
“…Upon transient transfection of 293T cells with GFP fusion proteins of NHSL1 fragments, we found that the 4 th fragment at the C-terminus of NHSL1 retrieved a large amount of PPP2R1A upon GFP immunoprecipitation (Fig.6a). The 2 nd fragment of NHSL1 that contains the two previously reported binding sites for the SH3 domain of ABI1 16 also retrieved PPP2R1A, but to a much lesser extent than the 4 th fragment. The AlphaFold2 software predicted with high confidence three motifs in fragment 4 that interact with the PPP2R1A scaffold or the PPP2R5D regulatory subunit retrieved in the WSC TAP (Fig.6b).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, NHSL1, NHSL2 and KIAA1522 also act to regulate actin assembly. A recent mechanistic study supports this hypothesis: NHSL1 localizes at the cell's leading edge and directly binds SCAR/WAVE to negatively regulate its activity, reducing F-actin content in lamellipodia and inhibiting cell migration (41). The authors identified NHSL1's SCAR/WAVE binding sites, and we find these sequences to be conserved in NSHL2 and KIA1522 (Fig.…”
Section: Interactome Analysis and Stoichiometry-driven Clusteringsupporting
confidence: 77%
“…Thus, NHSL1, NHSL2, and KIAA1522 might also act to regulate actin assembly. A recent mechanistic study supports this hypothesis: NHSL1 localizes at the cell’s leading edge and directly binds SCAR/WAVE to negatively regulate its activity, reducing F-actin content in lamellipodia and inhibiting cell migration ( 41 ). The authors identified NHSL1’s SCAR/WAVE binding sites, and we found these sequences to be conserved in NSHL2 and KIA1522 (Fig.…”
Section: Interactome Analysis and Stoichiometry-driven Clusteringmentioning
confidence: 91%